“Pele Alerta Project”: prevention and early detection of skin cancer aimed at beauty professionals - Caroline Kroeff Machado; Alessandra Haddad; Ivan Dunshee de Abranches Oliveira Santos; Lydia Masako Ferreira (Revista Brasileira de Cirurgia Plástica, 2021)
Introduction: Skin cancer is the most common neoplasm in several countries, including Brazil, and its incidence continues to rise. Early detection and primary prevention are the main ways to reduce morbidity and mortality. Places such as the head, neck and back are difficult to see by the person himself. There is a potential in beauty professionals for the early detection of these lesions and referral for evaluation and medical conduct. Objectives: Develop an online project with tools to educate beauty professionals about skin cancer. Methods: Based on current literature, videos and educational illustrated material were made available on a website. Results: The "Pele Alerta Project" can be accessed at www.projetopelealerta.com; this currently has four topics, each with a video (YouTube) and support material in PDF. Conclusion: The project in question is feasible, easy to execute and allows comprehensive education concerning skin cancer.